Signs and symptoms related to inhalation of surgical smoke in the nursing team - Ana Claudia Saito; Amanda Salles Margatho; Aryane Apolinario Bieniek; Nathanye Crystal Stanganelli; Renata Perfeito Ribeiro (Universidade Federal do Rio de Janeiro, 2019)
ABSTRACT Objective: To compare the prevalence of signs and symptoms related to inhalation of surgical smoke among surgical technologists and non-surgical technologists nursing professionals. Method: A cross-sectional study with 46 professionals from a university hospital. To evaluate the prevalence, an instrument with signs/symptoms related to the inhalation of electrocautery smoke was used. To verify the comparison between the prevalence of signs/symptoms, the Fisher's exact test was performed. Results: Higher prevalence of all signs/symptoms among surgical technologists, with a statistically significant difference between the act of instrumenting with the presence of at least one signs/symptoms related to inhalation of surgical smoke (p=0.01); eye irritation (p=0.02); irritation of nasal mucosa and oral cavity (p=0.03); headache (p=0.04). Conclusion: The presence of problems related to surgical smoke in nursing workers elicits more attention. Implications for practice: Health units must be aware of the risk of such exposure and take measures to preventing it.